Internal Audit Quality, Corporate Governance, and Corporate Social Responsibility: Determinants of Financial Reporting Quality - Suhita Whini Setyahuni; Nanda Adhi Purusa; Joni Prayogi; Miftachul Mujib (UMSurabaya Publishing, 2022)
This study intends to examine what factors were determined the quality of financial statements. We examined the impact of internal audit quality, corporate governance, and CSR performances on financial reporting quality. Since financial reporting quality was difficult to observe directly, we used the accrual earnings management (EM) approach. Using 78 firm-year observations of 39 public companies listed in the LQ-45 index from 2019 to 2020, We employed Ordinary Least Squares (OLS) regression as our data analysis technique. The number of audit committees and board size became the measurement indicators of internal audit quality and corporate governance. Moreover, CSR ratings provided by CSR Hub measured CSR performances. Our findings indicated a positive relationship between internal audit quality and corporate governance on the quality of financial performance. It means that both internal quality and corporate governance become the determinant factors of financial reporting quality. On the other hand, CSR performances did not have any relationship with the financial reporting quality. This paper provides fruitful insight into the factors that driven financial reporting quality. Using different aspects of factors influencing the quality of financial statements, we initially offer valuable insight for business practitioners and potential investors to assess the quality of financial performance